Transforming Pharmacy Students’ Perceptions of Diabetes: An Innovative Teaching Approach Using Patient Interviews and Photovoice - Jenifer Santos; Manuel Machuca (Pharmacy)
This study evaluated an innovative teaching methodology in a Health Anthropology course for Pharmacy students aimed at transforming their perceptions of diabetes. Through patient interviews and the photovoice technique, students gained deeper insights into the psychosocial aspects of the disease. Surveys were administered at the beginning, midpoint, and end of the course to assess shifts in students’ perspectives. The results revealed a significant change, with students evolving from a primarily biomedical view to a more holistic understanding, emphasizing the patient’s lived experience. Additionally, students responded positively to the innovative approach, citing enhanced motivation and learning, though some noted the methodology’s demanding workload. This teaching intervention fostered empathy and a broader perspective on the challenges faced by patients living with diabetes, supporting a more patient-centered and humanistic approach to healthcare. Despite the positive feedback, there was some uncertainty about whether this methodology could be applied to other subjects within the Pharmacy curriculum.